BREAST CANCER SURVIVAL AFTER SURGERY AND OTHER TREATMENTS: A LITERATURE REVIEW - Ramadhanti , Ismaya; Izzati , Mutiara Nur; Fitri , Asti Elysia Rahmatul; Rahmayanti , Verina Lutfiah; Hamid , Endah Nurhalimah; Hanifah , Laily (Journal of Public Health Research and Community Health Development, 2025)
Background: Breast cancer treatment has changed over the years, both surgically and medically. Purpose: This study aims to conduct a literature review on survival in breast cancer patients after undergoing surgery and other treatments. Methods: A literature review was conducted from the databases PubMed, ScienceDirect, and Google Scholar using the keywords "breast cancer," "surgical treatment" (OR surgery OR treatment option OR preference), and "survival analysis." The articles were identify using PICO approach with the study population were female breast cancer patients undergoing surgical intervention from all age groups and nationalities. The inclusion criteria were articles with free full text access in English and Bahasa with the range of the studies 2019-2024. The exclusion criteria were articles discussing surgical interventions for other type of cancer, breast cancer surgical intervention in male population, and qualitative studies or non-original research. Results: There were 39,299 articles reported in the PRISMA flowchart, 9,049 articles were duplicated articles, and 136 articles were excluded based on PICO. Ten articles were selected and included in this literature review to observe the survival between surgical treatment and other treatment among breast cancer patients. This study indicated differences in survival among breast cancer patients after receiving treatment. The combination of breast cancer surgery (BCS) and radiotherapy showed a better outcome compared to the combination of mastectomy and radiotherapy. Conclusion: Our review shows that survival of breast cancer patients may vary depending on the type of treatment given, hormonal status and cancer severity level.